2012
DOI: 10.1001/archfacial.2011.734
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Botulinum Toxin A on Cytokine Synthesis in a Cell Culture Model of Cutaneous Scarring

Abstract: The present data do not add evidence to suggest a significant therapeutic role of botulinum toxin A injections for cutaneous wound healing beyond chemoimmobilization. Further studies that include patient-specific cells of hypertrophic scars are required to better understand what role botulinum toxin A can play in the treatment of mature scar tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Chen (L. Chen et al, 2019) showed that BTA could reduce the proliferation and migration of fibroblasts through JNK pathway activation, and inhibit the protein expression levels of TGF-β, IL-6 and connective tissue growth factor (CTGF). In contrast, in a culture with dermal fibroblasts and microvascular endothelial cells, the above phenomenon was not observed (Haubner et al, 2012). Verapamil is also a controversial drug for scars.…”
Section: Synthetic Drugsmentioning
confidence: 89%
“…Chen (L. Chen et al, 2019) showed that BTA could reduce the proliferation and migration of fibroblasts through JNK pathway activation, and inhibit the protein expression levels of TGF-β, IL-6 and connective tissue growth factor (CTGF). In contrast, in a culture with dermal fibroblasts and microvascular endothelial cells, the above phenomenon was not observed (Haubner et al, 2012). Verapamil is also a controversial drug for scars.…”
Section: Synthetic Drugsmentioning
confidence: 89%
“…19 Furthermore, any concentration of BTXA seems to have no negative impact on normal skin tissue, confirming that BTXA targets only scar cell fibroblasts while leaving normal skin tissue unaffected. 20…”
Section: Mechanism Of Botulinum Toxin In the Treatment Of Scarsmentioning
confidence: 99%
“…Most authors have utilized fibroblasts that are derived from hypertrophic scars. Haubner et al, 34 investigated the effects of Botox on normal human skin fibroblasts and dermal micro-vascular endothelial cells. After incubating the cells with different concentrations of Botox, the toxin did not show any effect on the expression of cytokines or other growth factors (such as monocyte chemoattractant protein 2, fibroblast growth factors, macrophage colony-stimulating factor, and vascular endothelial growth factor).…”
Section: Botulinum Toxin In Wound Healing and Facial Scarringmentioning
confidence: 99%